The Use of E-Money to Implement Business Transactions of the Student of Madrasah Boarding School, West Bandung Regency - M A Asmara; R Wahdiniwaty; Hamidah; T Martini; Muhtarudin (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to find out how far the students of Madrasah Aliyah have used e-money in their daily lives, what transactions are carried out using e-money and (3) the experience felt when conducting e-money transactions. behavior towards business is a broad field to discuss, seeing how business segmentation is increasingly recognizing demographic boundaries. With the pandemic situation, the Indonesian people are required to be able to provide convenience in virtual transactions and not burden both consumers and business people. Seeing transactions that have switched to electronic transactions with various convenience features in paying for buying and selling activities, the issue of physical money will be replaced by electronic money. This is supported by the existence of products from financial institutions or banks that issue various forms of E-money or E-Wallet. to speed up the transfer of physical money into electronic money. Stores that provide payment facilities using E-money. For example Alfamart, Indomart, and other minimarkets that already provide cashless payment facilities. Obstacles that certainly exist in some areas of their children to be able to get the convenience of technology, one example is E-Money. Therefore, a qualitative analysis will be carried out on youth behavior policies that are constrained by the prohibition on the use of electronic facilities.